2016
DOI: 10.1007/s00266-016-0717-7
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Resorbable Skin Sutures: Story Retold!

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the A3 online Instructions to Authors. www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Unlike Alinasab and Haraldsson, we did not trim PG sutures postoperatively as it has been indicated that simple rubbing of these sutures after the 10th postoperative day results in their spontaneous fallout. 14 We also experienced exactly the same result. We also encountered no wound infection in either of the groups in our study.…”
Section: Discussionsupporting
confidence: 71%
“…Unlike Alinasab and Haraldsson, we did not trim PG sutures postoperatively as it has been indicated that simple rubbing of these sutures after the 10th postoperative day results in their spontaneous fallout. 14 We also experienced exactly the same result. We also encountered no wound infection in either of the groups in our study.…”
Section: Discussionsupporting
confidence: 71%
“…Whenever possible (i.e. in case of small surgical excisions/biopsies), we used dissolvable stitches to avoid post-surgical control (19,20). We preferred primary instead of secondary intention healing, especially in the peri-ocular/oral/nasal areas, to avoid surgical wounds adjacent to the respiratory/ocular tract capable of increasing COVID-19 vulnerability (21).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…We acknowledge the excellent study by Alinasab and Haraldsson [1] and the letter in response to the article by Choudhary et al [2]. Our unit has also experienced excellent outcomes with the use of absorbable sutures for the closure of the columellar incision during rhinoplasty cases.…”
Section: To the Editormentioning
confidence: 81%